Transcending racial barriers toward a mutual obligations approach - Emerson, Michael O., 1965-; Yancey, George A., 1962- (New York ; Oxford : Oxford University Press, 2011)
This work offers a balanced approach towards dealing with racial alienation. The book is a bold step forward in the debate about what sort of public policies can overcome the ethnocentrism inherent in so much of the racism we suffer from.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Racism -- United States -- History; Conflict management -- United States; United States -- Race relations